2015
DOI: 10.1080/2162402x.2015.1115940
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide enhances antitumor functions of chimeric antigen receptor modified T cells

Abstract: Tumor immunotherapy based on the use of chimeric antigen receptor modified T cells (CAR T cells) is a promising approach for the treatment of refractory hematological malignancies. However, a robust response mediated by CAR T cells is observed only in a minority of patients and the expansion and persistence of CAR T cells in vivo is mostly unpredictable.Lenalidomide (LEN) is an immunomodulatory drug currently approved for the treatment of multiple myeloma (MM) and mantle cell lymphoma, while it is clinically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 24 publications
(34 reference statements)
0
52
0
Order By: Relevance
“…One study found that lenalidomide has synergistic anti-tumor effects with CD19 CAR-T cells and CD20 CAR-T cells in treating B-Non Hodgkin’s lymphoma (B-NHL) [46]. …”
Section: Expectationmentioning
confidence: 99%
“…One study found that lenalidomide has synergistic anti-tumor effects with CD19 CAR-T cells and CD20 CAR-T cells in treating B-Non Hodgkin’s lymphoma (B-NHL) [46]. …”
Section: Expectationmentioning
confidence: 99%
“…Proposed mechanisms for this observation include of mobilization of malignant cells into blood by ibrutinib and/or reduction of expression of inhibitory receptors such as PD-1 [34]. Similar synergistic response is seen in models with the use of lenolidomide and CAR-T possibly via improved co-stimulation of CAR and/or favorable cytokine expression of IL2 and TNF gamma [39]. Large multi-center clinical trials with the use of CAR-T in MCL are currently underway including the TRANSCEND (NCT02631044) and ZUMA-2 (NCT02601313) trials.…”
Section: Mantle Cell Lymphomamentioning
confidence: 64%
“…Moreover, pembrolizumab proved to be safe and well tolerated, and only a slight fever was reported in 2 of the patients and no autoimmune toxicities were observed [93]. Other innovative approaches have been investigated such as the combination with lenalidomide [94], or indoleamine 2,3dioxygenase (IDO) inhibitors [95], highlighting how this field of research is continuously raising the bar moving toward a more personalized medicine.…”
Section: Tumor Immune Escape: the Cd19 Antigen Loss Issuementioning
confidence: 96%